The Dynamics of 3-dimentional micro-mechanic sensor of angle motions of a robot-hexapod - Osadchy, S.; Zozulya, V.; Rudiuk, G. (River Publishtrs, 2015)
Transfer function matrices of 3d MEMS sensor of angular motions and spectral density of noises measurements were estimated with the help of the method of structural identification for first time. This provides the possibility to control and operate the angle position of the platform of robot-hexapod.
Keywords: micro-mechanic gyroscope; angular motion; hexapod; identification; factorization; separation